Ethyl-acetate fraction from a cinnamon-cortex extract protects pancreatic β-cells from oxidative stress damage - Li, Weiling; Qiao, Jialu; Lin, Kuan; Sun, Ping; Wang, Yuansong; Peng, Qian; Ye, Xiansheng; Liu, Wei; Sun, Binlian (Frontiers in Pharmacology, 2023)
Background: The pathogenesis of diabetes mellitus is mediated mainly by oxidative stress produced by damaged pancreatic β-cells. We identified that an ethyl-acetate fraction (EA) from a cinnamon-cortex extract (CCE) is rich in flavonoid, and showed no toxicity to β cells. Objective: In this study, we evaluated the pharmacologic activities of EA on pancreatic β cells using a model of oxidative stress induced by H2O2 or alloxan. Results: The results showed that EA could significantly reduce reactive oxygen (ROS) accumulation to improve the survival of cells. Western blot showed that EA treatment upregulated expression of nuclear factor erythroid 2 related factor 2, heme oxygenase-1, and gamma glutamylcysteine synthetase. The same model study found that EA also can protect β cells against the apoptosis induced by oxidative stress. Furthermore, EA can enhance insulin secretion in rat and mouse β cell lines treated or not with alloxan or H2O2. The expression of the insulin transcription factor PDX-1 increased in an EA concentration-dependent manner. At last, the major functional compounds of EA analysis showed that three compounds, cinnamyl alcohol, coumarin, and cinnamic acid, had similar effects as EA. Conclusions: In sum, our data suggested that EA fraction from CCE can protect β cells from oxidative stress, and increase insulin secretion to improve the function of β cells. This function might be due to these three compounds found in EA. Our findings provide a theoretical basis and functional molecules for the use of CCE against diabetes mellitus.